FEATURES OF THE DEVELOPMENT OF TOOLS FOR PLANNING INNOVATION ACTIVITY OF ENTERPRISES - Gnylianska, Lesia; Zamostnyi, Volodymyr (SWorld-Ger Conference proceedings, 2025)
The peculiarities of the development of modern tools for planning the innovation activity of enterprises in the conditions of the digital economy are considered. Attention is focused on the integration of strategic, analytical and managerial approaches th